Targeted Discovery and Characterization of Type‐II PKS‐NRPS Hybrid DNA‐Alkylating Antibiotics - Nie, Qiu‐Yue; Fang, Shi‐Qi; Wu, Lian; Gao, Ruo‐Qin; Hu, Yu; Ding, Dian; Pan, Hai‐Xue; Pei, Zeng‐Fei; He, Jun‐Bin; Zhou, Qiang; Chen, Zi‐Hui; Hou, Xian‐Feng; et al. (Angewandte Chemie International Edition, 2025)
DNA alkylating natural products usually exhibit diverse bioactivity and serve as a crucial source of drug leads. Here, we employed genome mining guided by HTH‐42 superfamily resistance gene to precisely discover a new class of DNA‐alkylating antibiotics, xinghaicarcins, from Streptomyces xinghaiensis . They possess an intricate spiro‐epoxide‐bearing spiroketal heptacyclic scaffold fused with a pipecolic acid, assembled by a type II polyketide synthase–nonribosomal peptide synthetase hybrid system. An aminotransferase XhnB1 and a methyltransferase XhnM are identified to catalyze the formation of N‐methylated pipecolic acid building block, leading to the completion of the polyketide–peptide backbone. The identification of XhnM facilitated stereochemical determination of six chiral centers in xinghaicarcins by co‐crystallization. Notably, xinghaicarcins exhibit potent antibacterial activity against drug‐resistant pathogens and cytotoxicity against multiple cancer cell lines. Additionally, the HTH‐42 superfamily resistant protein, XhnU2, was characterized to mitigate xinghaicarcin‐induced genotoxicity. This work provides comprehensive insights into structure, biosynthesis, bioactivity, and self‐resistance mechanisms of xinghaicarcins, expanding diversity of DNA alkylating natural products.